Exercise preconditioning prevents MCT-induced right ventricle remodeling through the regulation of TNF superfamily cytokines. (15th January 2016) - Nogueira-Ferreira, Rita; Moreira-Gonçalves, Daniel; Silva, Ana Filipa; Duarte, José Alberto; Leite-Moreira, Adelino; Ferreira, Rita; Henriques-Coelho, Tiago
Abstract: Background: Exercise training has been recognized as a non-pharmacological therapeutic approach in several chronic diseases; however it remains to be tested if exercise preconditioning can positively interfere with the natural history of pulmonary arterial hypertension (PAH). This is important since the majority of these patients are diagnosed at advanced stages of the disease, when right ventricle (RV) impairment is already present. Objectives: In the current study, we evaluated the preventive effect of exercise preconditioning on RV failure secondary to PAH, with a focus on the signaling pathways modulated by pro-inflammatory cytokines from TNF superfamily. Methods: We analyzed the RV muscle from adult male Wistar rats exposed to a 4-week treadmill exercise training or sedentary regime, prior to the administration of monocrotaline (MCT) to induce PAH or with saline solution (controls). Results: Data indicate that exercise preconditioning prevented cardiac hypertrophy and RV diastolic dysfunction. At a molecular level, exercise modulated the TWEAK/NF-κB signaling axis and prevented the shift in MHC isoforms towards an increased expression of beta-MHC. Exercise preconditioning also prevented the increase of atrogin-1 expression, and induced a shift of MMP activity from MMP-9 to MMP-2 activity. Conclusions: Altogether, data support exercise as a preventive strategy for the management of PAH, which is of particular relevance for the familial form of PAH that is manifested by greater severity or earlier onset. Highlights: Exercise preconditioning prevents PAH-induced right ventricle dysfunction. This beneficial effect seems to be related with the prevention of cardiac hypertrophy, fibrosis and MHC isoform switch. Exercise preconditioning also modulates TWEAK/NF-κB signaling and proteolysis. The protective phenotype promoted by exercise preconditioning can be maintained for several days after cessation of exercise.